(untitled) (Collection of scientific works «Modern structures of metal and wood», 2025)
The article presents the results of numerical modeling and stress-strain state analysis of frame roofs of vertical cylindrical tanks with conical and spherical geometries. A comparative analysis of the efficiency of various structural solutions was carried out, considering both the presence and absence of the roof sheathing in finite element models. Analytical calculation methods are complex, labor-intensive, and not always suitable for practical application. On the contrary, quite often, in convenient numerical calculation tools, models are simplified, which leads to unreliable results: underestimation or overestimation of stresses and deformations in load-bearing elements of coatings. In view of this, there is a need to study the impact of such simplifications on the accuracy of calculations and to justify their feasibility. This study looked at roofing options without a central support. According to current design standards, when calculating the covering of a vertical cylindrical tank, it’s important to consider how the frame elements and sheet flooring work together. It was found that simplification of calculation schemes without modeling the sheathing leads to a significant overestimation of internal forces and deformations in the frame elements. Critical factors were identified for the main load-bearing components depending on the tank diameter, which allows substantiating the choice of roof type and rational structural solutions to improve the reliability and efficiency of steel tanks. The obtained results can be used to improve engineering calculation methods and optimize structural schemes of frame roofs in the design of large-diameter tanks.